PENGARUH PENERAPAN METODE BRAINSTORMING TERHADAP KEAKTIFAN BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 13 PALEMBANG - Yuliani Kartika Putri; Djahir Basir; Ikbal Barlian (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2016)
This study aims to determine whether there are differences in methods of brainstorming with quatum method of learning to students' learning activeness on economic subjects in SMAN 13 Palembang. The population in this study were students of class X MIA in SMAN 13 Palembang which consists of 6 classes totaling 243 students. The research sample using random cluster sampling, so that the selected class X MIA 1 totaling 40 students as an experimental class and class X MIA 2 totaling 40 students as the control class. Data collection techniques such as observation aims to determine the application of methods of brainstorming with quatum method of learning to students' learning activeness, while the questionnaire is used as supportive data from the observation, questionnaire given at the last meeting. The data analysis technique used to test the hypothesis using t-test was obtained thitung 3,69 ≥ ttabel 1,98. Based on the results of this study concluded that there are differences in the effect of applying methods of brainstorming with quatum method of learning to students' learning activeness with the results of experimental observation average grade 83.63% with a good category while the average grade control 69.70% with a category quite well while the results of the questionnaire average class experiment 51.45% while the average of 49.8% of control class questionnaire. Based on the conclusion, it is suggested for further research in order to pay attention to the obstacles in this research that when the focus groups did not refer to the students' learning activeness.